Antimicrobial resistance in bacterial sexually transmitted infections. (May 2022) - Pitt, Rachel; Fifer, Helen
Abstract: Antimicrobial resistance (AMR) in bacterial sexually transmitted infections (STIs) is a global public health concern. Neisseria gonorrhoeae and Mycoplasma genitalium are emerging 'superbugs' that have developed AMR to all antimicrobials used in their treatment, and treatment failures have been reported. There is a very real threat that these infections could become untreatable in the future. Although syphilis and chlamydia infections are easily treated with first-line antimicrobials, macrolide resistance has emerged in Treponema pallidum, and there is a concern that AMR could potentially develop in Chlamydia trachomatis . Strengthened global AMR surveillance, antibiotic stewardship and reporting of treatment failures, together with improved diagnostics, new therapeutics and vaccines, are essential to maintain effective treatment and reduce the burden of STIs.